Pengaruh CRM dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan dan Keputusan Pembeli yang Dimediasi oleh Kepuasan Dan Kepercayaan Pelanggan Studi pada PT Yekape Surabaya (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the influence of Customer Relationship Management (CRM) and service quality on customer loyalty and purchasing decisions through customer satisfaction and customer trust at PT YEKAPE Surabaya. This research employed a quantitative approach using an associative research method. The population consisted of all customers of PT YEKAPE Surabaya. The sampling technique used purposive sampling with a total of 100 respondents. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS software. The results showed that CRM and service quality have a positive and significant effect on customer satisfaction and customer trust. Customer satisfaction and customer trust also have a significant effect on customer loyalty and purchasing decisions. In addition, customer satisfaction and customer trust were proven to mediate the relationship between CRM and service quality on customer loyalty and purchasing decisions. This study concludes that improving CRM and service quality is very important in increasing customer loyalty and purchasing decisions at PT YEKAPE Surabaya.